Embedding Content or Interring Copyright: Does the Internet Need the “Server Rule”? - Ginsburg, Jane; Budiardjo, Luke Ali (The Columbia Journal of Law & the Arts, 2019)
The “server rule” holds that online displays or performances of copyrighted content accomplished through “in-line” or “framing” hyperlinks do not trigger the exclusive rights of public display or performance unless the linker also possesses a copy of the underlying work. As a result, the rule shields a vast array of online activities from claims of direct copyright infringement, effectively exempting those activities from the reach of the Copyright Act. While the server rule has enjoyed relatively consistent adherence since its adoption in 2007, some courts have recently suggested a departure from that precedent, noting the doctrinal and statutory inconsistencies underlying it. Authors and copyright owners have long lamented that the server rule’s immunization of certain online activities eviscerates their ability to control how their works are disseminated on the Internet. But many Internet users and commercial actors have incorporated the rule’s liability shield into their expectations about how the Internet does (and should) function. Accordingly, while authors and copyright owners foresee improved prospects for remuneration, many commentators and advocacy groups have expressed concerns regarding the recent judicial doubt about the validity of the server rule. They contend that, without the server rule, the Internet would cease to function as it does today. However, these concerns overlook the applicable defenses—in particular, the defenses of safe harbor under § 512 of the Digital Millennium Copyright Act and express license—which, we expect, would take on a more significant role in a post- server rule world. In this Article, we explore the likely effect of the potential reversal of the server rule, taking into account these defenses. We conclude that the principal difference between copyright law with and without the server rule comes down to the author’s ability to obtain the removal of links to infringing content, and to authorize embedding of content from a source to which the public had lawful access. Moreover, while the reversal of the server rule may interrupt a handful of online services that rely entirely on the unauthorized appropriation of copyrighted works, most online practices would likely continue unaltered in the post-server rule world.